Acoustic reflex on newborns: the influence of the 226 and 1,000 Hz probes - Lilian Cássia Bórnia Jacob-Corteletti; Josilene Luciene Duarte; Fernanda Zucki; Luciane Domingues Figueiredo Mariotto; José Roberto Pereira Lauris; Kátia de Freitas Alvarenga (CoDAS)
PURPOSE: To analyze the occurrence of acoustic reflex and its threshold on newborns using the 226 and 1,000 Hz probes. METHODS: Thirty-six newborns with "PASS" results in newborn hearing screening and tympanogram with one or two peaks for both probe tones were included. Group I comprised 20 full-term newborns without risk indicator for hearing loss, and Group II comprised 16 newborns with at least one risk indicator. The study about ipsilateral acoustic reflex thresholds was conducted in 500, 1,000, 2,000, and 4,000 Hz. RESULTS: The groups presented the acoustic reflex thresholds between 50 and 100 dB for both probe tones. In the comparison between the probes, there were differences in all frequencies evaluated in Group I, with the lowest threshold mean for the 1,000 Hz probe. In Group II, differences were detected at 2,000 Hz. The mean acoustic reflex thresholds were similar in both groups for the 226 Hz probe. There was a difference for the 1,000 Hz probe in all tested frequencies. The percentage of response was higher in both groups for the 1,000 Hz probe. The kappa test showed extremely poor agreement in the comparison of results between both probes. CONCLUSION: The occurrence of acoustic reflex was higher in newborns and its thresholds were lower with the 1,000 Hz probe both for healthy newborns and for newborns at risk.